2014
DOI: 10.1350/pojo.2014.87.1.649
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of the Special Constabulary: Are Forces Getting Value for Money from Their Voluntary Officers? An Empirical Study in Avon and Somerset Police

Abstract: The aim of this paper is twofold. First, to explore whether Avon and Somerset Police can get better value for money from the Special Constabulary by increasing officer retention and second, and perhaps more importantly, to stimulate debate and highlight the apparent dearth of research and evidence pertaining to the Special Constabulary at a time of rapid expansion. Based on personal experience as a Special Constable and empirical research conducted in 2012 within Avon and Somerset Police, this paper considers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 3 publications
3
35
0
Order By: Relevance
“…Previous research has shown that volunteer police officers regularly donate in the region of 25 to 30 hours a month to their part-time voluntary roles (Whittle 2014;Pepper and Wolf 2015). However, what isn't clear is the division between hours that are donated for operational front-line services as a policing resource as opposed to involvement in professional development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that volunteer police officers regularly donate in the region of 25 to 30 hours a month to their part-time voluntary roles (Whittle 2014;Pepper and Wolf 2015). However, what isn't clear is the division between hours that are donated for operational front-line services as a policing resource as opposed to involvement in professional development.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the actions of salaried police constables came to displace those of volunteers (Crawford, 1999;Emsley, 2011), they did not entirely supersede them. For example, Special Constabularies -which comprise uniformed volunteer constables with full police powers (see Seth, 1961;Leon, 1991;Mirrlees-Black and Bryon, 1994;Gaston and Alexander, 2001;Whittle, 2014;Bullock, 2014;Bullock and Leeney, 2014) -have been formally allied to regular constabularies since the mid-19 th century. The special constable was traditionally retained by constabularies as a 'reserve' to be deployed in times of emergency (Seth, 1961;Leon, 1991;Mirrlees-Black and Bryon, 1994) and today supplements and reinforces day-to-day police work in wide-ranging ways (Whittle, 2014;Bullock and Leeney, 2014).…”
Section: Volunteers and The Police Servicementioning
confidence: 99%
“…For example, Special Constabularies -which comprise uniformed volunteer constables with full police powers (see Seth, 1961;Leon, 1991;Mirrlees-Black and Bryon, 1994;Gaston and Alexander, 2001;Whittle, 2014;Bullock, 2014;Bullock and Leeney, 2014) -have been formally allied to regular constabularies since the mid-19 th century. The special constable was traditionally retained by constabularies as a 'reserve' to be deployed in times of emergency (Seth, 1961;Leon, 1991;Mirrlees-Black and Bryon, 1994) and today supplements and reinforces day-to-day police work in wide-ranging ways (Whittle, 2014;Bullock and Leeney, 2014). More generally, citizens have been implored to take responsibility for their own security and that of their neighbourhoods and encouraged to work proactively with constabularies to resolve problems at the local level in contemporary times (Garland, 1996;Crawford, 1999;Bullock, 2014).…”
Section: Volunteers and The Police Servicementioning
confidence: 99%
“…As Bullock and Leeney (2014: 485) argue, in the UK context, ‘we know little about the motivations and experiences of those who volunteer. Nor do we know much about how the Special Constabulary operates in practice, the management and regulation of this sizable volunteer force.’ A relatively small number of research studies have been published in respect of the experiences of volunteer officers (Britton, Callender and Cole, 2016; Bullock and Leeney, 2014; Gaston and Alexander, 2001; Gill and Mawby, 1990; Hieke, 2017; Leon, 1991, Mirrlees-Black and Byron, 1994; National Policing Improvement Agency (NPIA), 2010; Pepper, 2014; Pepper and Wolf, 2015; Whittle, 2014; Wolf, Holmes and Jones, 2015; Wolf, Pepper and Dobrin, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although the body of literature exploring the experiences of volunteer police officers remains relatively small, and some of the studies are now quite dated, the literature has been consistent in terms of several key findings. There is a consistent theme of the limitations or inadequacies of Special Constable training (Bullock and Leeney, 2014; Gaston and Alexander, 2001; Gill and Mawby, 1990; Leon, 1991, Mirrlees-Black and Byron, 1994; NPIA, 2010; Whittle, 2014), with the perceptions of Special Constables that their training has not prepared them sufficiently and that the transition into practice is not well managed and supported (Whittle, 2014). Cultural challenges are identified consistently (Bullock and Leeney, 2014; Gaston and Alexander, 2001; Gill and Mawby, 1990; Leon, 1991, Mirrlees-Black and Byron, 1994; NPIA, 2010), with what is referred to by Gill and Mawby (1990: 131) as an ‘undercurrent of scepticism’ among Regulars in respect of Special Constables.…”
Section: Introductionmentioning
confidence: 99%